Strategi Pemasaran Wisata Kuliner Sebagai Destinasi Wisata Di Dili, Timor-Leste - Nheu, Grace Deo Seldudes Eta; Sugiarti, Dian Pramita (JURNAL DESTINASI PARIWISATA, 2020)
These project are done for  discussing the culinary tourist marketing at the tourism industry by identifying some of  East Timor’s traditional foods that could be developed as a culinary destination. Local culinary has a good potential to be developed and can be used as a tourist product to attract tourist for a pay visit in East Timor by the reason of foods and drinks diversity and in East Timor. The purpose of this project is to know the culinary tourist marketing as a tourism business and attract tourists in Dili, East Timor. Data gathering techniques which is used to collects in this project are observation, interview, and documentary studies and this project using primary and secondary data.  The study also employs qualitative data and will be analysis with qualitative techniques methods of marketing and is made up on four (4p) marketing structure. In this project has been used concepts that are related like marketing strategies, the culinary tours, the traditional foods, tourist destination, gastonomic theory, and marketing theory. The conclusion on these research are to discover certain local culinary potential that have been exploited as a culinary tourist destination. Tourist marketing that could developed tradional foods from East Timor should be give to East Timor’s sustainability. Keywords :   Marketing Strategies, Culinary Tourism, Traditional Food.